ANALYSIS OF FACTORS INFLUENCING RISK MANAGEMENT STRATEGY AND SUSTAINABILITY OF SMALLHOLDER OIL PALM PLANTATION BUSINESSES IN ACEH JAYA REGENCY - Andya Safrizal; Indra; Monalisa (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The existence of smallholder oil palm plantations has become the cause of various risks that have a negative impact on the social, economic, and environmental aspects of the community, so it is necessary to have appropriate risk management strategies and the implementation of sustainable cultivation practices to support the existence and sustainability of smallholder oil palm plantation businesses. This study aims to analyze the factors that affect the risk management strategy and sustainability of smallholder oil palm plantations in Aceh Jaya Regency. This study uses a quantitative descriptive method. The population in this study is smallholder oil palm farmers in Aceh Jaya Regency, with a sample of 100 respondents consisting of 47 oil palm farmers in Teunom District and 53 oil palm farmers in Indra Jaya District, which were taken using the multi-stage cluster random sampling method. The data was analyzed using the Structural Equation Model (SEM) method, which was analyzed using the Smart PLS 4.0 application. The results show that farmers' perceptions and risk impacts have a positive and significant effect on risk management strategy. Farmer characteristics have a negative and significant effect on sustainability. Farmer perception, and risk management strategy has a positive and significant effect on sustainability.